The evaluation of lecturer's improvement programs through academic culture and services - Chairunnisa, Connie; Istaryatiningtias, Istaryatiningtias (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
This study evaluated the program to improve postgraduate lecturers' performance at Muhammadiyah University Prof. Dr. Hamka (UHAMKA). This study used a mixed-method sequential explanatory design. The primary data were collected using questionnaires for lecturers, study program coordinators, and students. The primary data were presented by observations and interviews with the Director of UHAMKA Postgraduate. The data analysis was carried out using differential statistics to support the interview and documentation results. The most prominent result was the Institute's concern for the lecturer problem, with the respondents' answers showing strong concern (13%), concern (45.7%), and immediate concern (41.3%). The Institute's concern for lecturer problems was not high. Therefore, it needs to be increased. This study implied the need to conduct a follow-up program by motivating lecturers without functional positions to be immediately concerned and collect the required documents.